PELAKSANAAN FUNGSI-FUNGSI MANAJEMEN DALAM PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM - Ramdanil Mubarok (Al-Rabwah, 2019)
The implementation of management functions is very important to regulate all activities, both formal and informal activities. An Islamic educational institution requires good management planning. Whether or not an Islamic educational institution is determined by how the implementation of management functions in the educational institution. In reality, the problems faced by Islamic educational institutions are so diverse. Starting from management problems, leadership problems, human resources, financial, and institutional problems. Good management certainly refers to the management functions themselves, where the intended functions are none other than POAC. Management must be applied in an effort to improve the quality of Educational Institutions because by applying management aspects such as planning, organizing, actuating, and controlling, the quality of educational institutions can be improved because of the implementation of management functions in a planned manner, systematic, sustainable and achieve the goals that have been created in this case educational institutions can achieve predetermined quality standards of education. Improving the quality of educational institutions can be achieved through the collectivity of the education system which involves various aspects such as curriculum, educational policies, materials, strategies, approaches and methods of learning, facilities, facilities and infrastructure, educators and education staff, managerial processes carried out professionally, the learning process, application of information and communication technology, especially in the learning process in the classroom, appropriate evaluation and control and quality control of education. Quality in educational institutions to ensure the quality of school inputs, processes, outputs and outcomes so as to increase the accountability of educational institutions.